(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
This study investigates the causes of salinity intrusion by disaster (such as SIDR) in the south-western parts of Bangladesh. The present research work was conducted in the Khulna and Satkhira district’s rivers like Rupsa, Vadra, Sibsa, Betna, Kholpetua and Morischap and other specific study area was at Gabura and Buri Goalini union of Shyamnagar upazilla under Satkhira district of Bangladesh from June to November, 2015. Salinity intrusion is a major problem and is found increasing day-by-day in the south-western parts of Bangladesh. For this study, data are collected from Bangladesh water development board (BWDB, Dhaka), and through reconnaissance survey with focus group discussion (FGD) in the Gabura and Buri Goalini union under Shyamnagar upazilla of Satkhira district. The data show that the EC and Chloride value in the study area were in the increasing state after SIDR because of the increasing temperature and decreasing rainfall and these values exceed the standard level of Bangladesh and WHO guideline. Further research is to be directed to acquire and quench pursuing to the crucial causes through factorization in a relation to salinity intrusion and disaster issues in the south-western parts of Bangladesh. Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 297-308